The Deviant Body in Neo-Victorian Literature: A Somatechnical Reading of The Freak in Rosie Garland’s The Palace of Curiosities (2013) - Pettersson, Lin Elinor (Universidad de la Rioja, 2016)
The contemporary fascination with historical, social and literary representations of the deviant body calls for new understandings of corporeality that question the body as a purely biological entity, and invites readings of corporeality as culturally inflected. The present article explores neo-Victorian enfreakment through the lens of “somatechnics” reading “[e]mbodiment as the incarnation or materialisation of historically and culturally specific discourses and practises” (Sullivan and Murray 2014: 3). I will apply the concept of somatechnics to (neo-)Victorian enfreakment practises drawing on scholars as Bordo (1993), Grosz (1994), Sullivan and Murray (2014) who, among others, have challenged the binary split between the mind and body, and argued for the social construction of embodied subjectivities. Although the body’s physical materiality is irreducible, the body is always invested, shaped and transformed by external forces, or “technologies of power” as denominated by Foucault (2003a). I seek to address the human exhibit in Rosie Garland’s The Palace of Curiosities (2013) to examine neo-Victorian reinventions of the divergent body. With this objective in mind, I will analyse how the neo-Victorian mode interlocks the Victorian freak-show discourse with the reader perspective to bring subjective responses to corporeality, humanity and normativity to the forefront, and in doing so, turns an exploitative space as the freak show into a site of self-reliance, self-expression and even fulfilment.
El Cuerpo Aberrante En La Literatura Neo-Victoriana: La Figura Del Freak A Través De La Somatecnología En The Palace Of Curiosities (2013) De Rosie Garland
Keywords: Literatura inglesa - 18..; Neo-Victorianism; Body; Freak Show; Somatechnics; Embodied subjectivity